2016
DOI: 10.20402/ajbc.2016.0063
|View full text |Cite
|
Sign up to set email alerts
|

Development of Whitening Cosmetic Ingredients from Cudrania tricuspidata Stem Extract

Abstract: This study was conducted to investigate the possibility of Cudrania tricuspidata (C. tricuspidata) stem extract as whitening cosmetic material. Methods: We performed TLC and HPLC analysis to investigate the anti-oxidant compounds and its contents in C. tricuspidata stem extract fractions (hexane, ethyl acetate, butanol, and water). In order to evaluate anti-oxidant effects, radical and superoxide scavenging activities were conducted by using DPPH, ABTS free radicals and xanthine oxidases, respectively. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…Accumulated studies have revealed that the extracts and components of C. tricuspidata exhibited a broad spectrum of pharmacological activities, including anti-inammatory, 22,23 antioxidant, 78,79 antitumor, 16,24 hepatoprotective, 25,26 neuroprotective, 27,28 antiobesity, 18,19 immunomodulatory, 70,71 antiatherosclerotic, 80,81 antimicrobial, 11,76 skin-protecting, 79,82 and antidiabetic 21,52 effects. The presence of a variety of bioactive compounds may be synergistically or individually responsible for the various activities of this species (Fig.…”
Section: Pharmacological Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulated studies have revealed that the extracts and components of C. tricuspidata exhibited a broad spectrum of pharmacological activities, including anti-inammatory, 22,23 antioxidant, 78,79 antitumor, 16,24 hepatoprotective, 25,26 neuroprotective, 27,28 antiobesity, 18,19 immunomodulatory, 70,71 antiatherosclerotic, 80,81 antimicrobial, 11,76 skin-protecting, 79,82 and antidiabetic 21,52 effects. The presence of a variety of bioactive compounds may be synergistically or individually responsible for the various activities of this species (Fig.…”
Section: Pharmacological Propertiesmentioning
confidence: 99%
“…82 The EtOAc fraction (IC 50 ¼ 24.4 ppm) and the n-BuOH fraction (IC 50 ¼ 88.3 ppm) of the C. tricuspidata stem extract could reduce the activity of tyrosinase and the melanin content in a concentrationdependent manner. 79 It was found that the avonoids steppogenin (149, IC 50 ¼ 2.52 mM) and trans-dihydromorin (160, IC 50 ¼ 21.54 mM) and the phenylpropanoid oxyresveratrol (IC 50 ¼ 2.85 mM) from the twigs of C. tricuspidata displayed potent inhibitory activities against mushroom tyrosinase and the melanogenesis process in melanocytes, which suggested their potential to be developed as skin-whitening agents in cosmetics and antibrowning agents in food. 75 The tyrosinase-inhibiting activity of the avonoids could be affected by the hydroxyl groups substituted at the 2-and 4-positions of the aromatic ring.…”
Section: Skin Protectionmentioning
confidence: 99%
“…Cudrania tricuspidata has traditionally been used as a medicinal plant for conditions including eczema, tuberculosis, and chronic back pain [ 1 ]. According to previous studies, the plant has many beneficial characteristics, including antioxidative [ 2 ], antimicrobial [ 3 ], antitumor [ 4 ], antiobesity [ 5 ], anti-osteoarthritis [ 6 ], antiaging [ 7 ], antiinflammatory, and neuroprotective [ 8 ] properties. It also shows efficacy against cardiovascular diseases [ 9 ] such as atherosclerosis and hypertension [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…최근 천연 소재를 활용한 기능성 화장품의 소재 개발 연구가 진행되고 있으며 (Ha & You, 2016;Han et al, 2016;Yu & Kim, 2017) (Lim et al, 2003 Tween 20, pH 7.5)]에 희석한 β-actin primary antibody…”
unclassified